Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3892/etm.2016.2971
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of microRNA-503 and reduced expression of kangai-1 in B-cell non-Hodgkin's lymphoma

Abstract: The aim of the present study was to determine the expression levels of microRNA-503 (miR-503) and the tumor suppressor gene, kangai-1 (KAI1), in B-cell non-Hodgkin's lymphoma (B-NHL). A total of 45 patients with B-NHL (including 29 cases with stage III/IV disease and 16 cases with stage I/II disease) were enrolled in this study. In addition, 26 patients with reactive lymphoid hyperplasia (RLH) were enrolled as the control patients. Reverse transcription-quantitative polymerase chain reaction was performed in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Until now, the function studies of miR‐503 mainly focus on the tumor biology behaviors such as its occurrence, development, invasion, and metastasis (Zhou et al, ; Li et al, ; Long et al, ). Meanwhile, recent study also revealed that accompanied with reduced expression of KAI1, miR‐503 expression was significantly increased in B‐cell non‐Hodgkin's lymphoma (B‐NHL) patients, indicating that it may be applied as a novel therapeutic and diagnostic marker (Wu et al, ). MiR‐503 also functions as an important epigenetic regulator to promote cardiac fibrosis via miR‐503‐Apelin‐ 13‐TGF‐β‐CTGF‐collagen production pathway (Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the function studies of miR‐503 mainly focus on the tumor biology behaviors such as its occurrence, development, invasion, and metastasis (Zhou et al, ; Li et al, ; Long et al, ). Meanwhile, recent study also revealed that accompanied with reduced expression of KAI1, miR‐503 expression was significantly increased in B‐cell non‐Hodgkin's lymphoma (B‐NHL) patients, indicating that it may be applied as a novel therapeutic and diagnostic marker (Wu et al, ). MiR‐503 also functions as an important epigenetic regulator to promote cardiac fibrosis via miR‐503‐Apelin‐ 13‐TGF‐β‐CTGF‐collagen production pathway (Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%